Pipistrellus pygmaeus ... - Toffoli, Roberto; Culasso, Paola; Locatelli, Andrea G.; Giraudo, Luca (Zenodo, 2016)
Pipistrellus pygmaeus (Leach, 1825) Risk Level Europe: Least Concern - LC (Temple & Terry, 2007). Italy: Data Deficient - DD (Rondinini et al. 2013). This species was only observed in Valdieri municipality, where single individuals were surveyed during hunting alongside the Gesso river between August and September. A temporary roost, used by at least 2 individuals, was found in a bridge in the same locality. ... : Published as part of Toffoli, Roberto, Culasso, Paola, Locatelli, Andrea G. & Giraudo, Luca, 2016, Bats of Alpi Marittime Nature Park (North West Italy) and Site of Community Importance IT 1160056: distribution and status, pp. 3-13 in Natural History Sciences 3 (1) on page 10, DOI: 10.4081/nhs.2016.254, http://zenodo.org/record/12523731 ...